SMART IRRIGATION SYSTEM PROTOTYPE FOR RICE PLANTS USING THE AWD METHOD - Ideva Gaputra; Harfebi Fryonanda; Ulya Ilhami Arsyah; Yori Adi Atma (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Irrigation is a system for irrigation in the form of waterways used to distribute water. In fulfilling the need for water, especially in rice farming, it is necessary to increase agricultural yields and reduce crop failure. All of that can be done with a well-controlled irrigation system to increase agricultural profits. Irrigation systems, especially in rice farming, have irrigation systems that have been widely implemented in Indonesia and have been proven to increase agricultural yields. The farming system is called the wet-dry irrigation system. To control the irrigation system and to be able to monitor it regularly, an IoT-based irrigation system was created. The device used for the main control is Arduino Uno. The results of the smart irrigation system produce a prototype that can control irrigation based on soil moisture and close irrigation using a water level sensor. After creating the prototype of the IoT device, the process of irrigating the land can be carried out automatically according to the wet and dry irrigation system, and monitoring the condition of irrigating rice fields via the internet can be carried out to increase the effectiveness of farming